Concepts of Politics and Government in Islamic Study - Ii Sumantri (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The study found that: (1) political thinkers of Islam agree that Islam requires the state to grounding its teaching through three approaches, Shari'ah, philosophical-theological, and human functional; implementation of the government is based on the basic principles of political Islam that are contained in the Al-Qur'an and Al-Sunnah, the Islamic political and historical facts at the time of the Prophet Muhammad and Khulafa al-Rasyidin Caliphs and (2) that the Al-Qur'an and Al-Sunnah do not explicitly mention the country (daulah), but only its basic principles. It can be understood that the muslim community, at any age and place, can implement these principles in a government system that varies from generation to generation